PENEGAKAN HUKUM TERHADAP PENGGUNAAN SEMPADAN PANTAI WURING DAN DAMPAKNYA BAGI LINGKUNGAN HIDUP DI KABUPATEN SIKKA - Maran, Mary Grace Megumi (Penerbit Universitas Atma Jaya Yogyakarta, 2024)
The coastal strip is one of the elements regulated in the regulation of spatial planning. The coastal strip is also a protected area of local protection type. However, there are still many people who do not pay attention and comply with the status of the coastal boundary area and the regulations governing the coastal boundary. One of them is done by the people of Kampung Wuring because they have used the coastal boundary for settlements. Therefore, this research discusses how the regulation of the coastal boundary in the Regional Regulation of the RTRW of Sikka Regency, how law enforcement against the use of the Wuring coastal boundary in Sikka Regency, and what environmental impacts are caused by the use of the Wuring coastal boundary in Sikka Regency. This research is a type of empirical legal research with qualitative data analysis method. The conclusion of this research is that Wuring Village is one of the locations designated as a coastal border area of Sikka Regency based on the Regional Regulation of Sikka Regency RTRW. However, in its implementation, the use of the Wuring coastal boundary is more focussed on residential activities. The Wuring coastal boundary follows the national legal regulation of 100 metres from the highest tide point inland. The area has been filled with houses, and the houses even protrude further into the sea. It is also known that the law enforcement implemented by the local government on the use of the Wuring coastal boundary is in the form of building restrictions. The use of the Wuring coastal boundary also causes impacts on the environment consisting of robb flooding, abrasion, pollution due to waste, pollution due to garbage, mangroves are decreasing, and coral reefs are damaged.